Kapampangan cusine in Angeles City: an indicator to tourist arrival in Pampanga - Abalos, Eugene C. alsol, Joseditha P. Caragan, Keid Marie D. Favila, Margot Jane S. Victoria, Kathleen Mae A 4 0 16; 5 (2014)
ABSTRACT This research was made to determine the significant relationship of Kapampangan Cuisine being served in Angeles City from tourist arrivals and promotional tools. The result of this study aims to help Pampanga to utilize their local cuisine for development and promotion. Researchers want to find out the distribution of managers and employees in the local restaurants in Angeles City; Kapampangan Cuisine being served the most; and the relationship of the number of Kapampangan Cuisine being served by the local restaurants in Angeles City from tourist arrivals and promotional tools. The respondents were managers from the local restaurants in Angeles City. The result of the study was analyzed and interpreted using percentage, frequency, ranking and Pearson's r correlation. Tables and figures were used to clearly show the results of the study.
Undergraduate Thesis: (B.S. in Travel and Tourism Management) - Pamantasan ng Lungsod ng Maynila 2014.
Keywords: 2 -- 0; 6; 20; 20; 2